Strategies used in translating English idioms into Chinese in the Oxford idioms dictionary / Yu Shuai - Yu, Shuai (2019)
Idioms are widely used in people’s daily lives, and thus have a profound influence on our language. An idiom is a group of words in a fixed order that has a particular meaning that is different from the meanings of each word on its own. This study on idioms will employ a qualitative method where the source text (ST) and target text (TT) will be compared and contrasted. Data are collected from Oxford Idioms Dictionary (English-Chinese Edition) and are categorized according to Nida’s cultural category (1945) which includes (1) ecology, (2) material culture, (3) social culture, (4) religious culture, and (5) linguistic culture. The origin of each idiom is used to determine its cultural category. Based on Baker’s translation strategies (1992) which are (1) using an idiom of similar meaning and form, (2) using an idiom of similar meaning but dissimilar form, (3) translation by paraphrase, and (4) translation by omission, the translation strategies are then identified. The example sentences containing the idioms in this dictionary will also be used as data. The translation strategy is identified by comparing and contrasting how each idiom is translated from English to Chinese. This will enable us to identify which translation strategy is most frequently used and which cultural category contains the most idioms. Lastly, the differences between the origins of the English idioms and the origins of the Chinese idioms are discussed to better understand these idioms. The findings of this study show that most of the selected idioms belong to social culture. Readers, who want to get more information about the background of English idioms, can check out sports and entertainment activities, such as horse racing, poker, boxing, cricket, running, football, basketball, and wrestling. They can better understand the origins of idioms by reading the Bible, Greek mythology, The Fables of Aesop, Shakespeare’s play and One Thousand and One Night. The difference between the origins of these two idioms is that the origins of most Chinese idioms are from linguistic culture while English idioms are from five cultural categories. Three out of four translation strategies as proposed by Baker have been found in the selected data. These three translation strategies are translation by paraphrase, translation by using an idiom of similar form and meaning, translation by using an idiom of similar meaning but dissimilar form. Other translation strategies found were literal translation, translation by using two idioms of similar meaning but dissimilar form, literal translation plus an idiom of similar meaning but dissimilar form. Translation by paraphrase is the most common translation strategy used in translating English idioms into Chinese. 74% of the selected idioms were translated using this strategy. The findings also show that the onus is on the translators to choose the translation strategy suitable for translating English idioms into Chinese.